Role of glucocorticoid negative feedback in the regulation of HPA axis pulsatility. (3rd September 2018) - Gjerstad, Julia K; Lightman, Stafford L; Spiga, Francesca
Abstract: The hypothalamic–pituitary–adrenal (HPA) axis is the major neuroendocrine axis regulating homeostasis in mammals. Glucocorticoid hormones are rapidly synthesized and secreted from the adrenal gland in response to stress. In addition, under basal conditions glucocorticoids are released rhythmically with both a circadian and an ultradian (pulsatile) pattern. These rhythms are important not only for normal function of glucocorticoid target organs, but also for the HPA axis responses to stress. Several studies have shown that disruption of glucocorticoid rhythms is associated with disease both in humans and in rodents. In this review, we will discuss our knowledge of the negative feedback mechanisms that regulate basal ultradian synthesis and secretion of glucocorticoids, including the role of glucocorticoid and mineralocorticoid receptors and their chaperone protein FKBP51. Moreover, in light of recent findings, we will also discuss the importance of intra-adrenal glucocorticoid receptor signaling in regulating glucocorticoid synthesis.